Magnesium sulfate, dexmedetomidine, and lignocaine in attenuating hypertension during laparoscopic cholecystectomy: a comparative study - Ismail M.A Ahmed; Hesham S Abdelraouf (Wolters Kluwer Medknow Publications, 2018)
Background Pneumoperitoneum during laparoscopic surgery is associated with significant hemodynamic changes represented by increasing heart rate, vascular resistance, and blood pressure. This study aimed to compare the safety of each of magnesium sulfate, dexmedetomidine, and lignocaine on hemodynamic responses during pneumoperitoneum. Patients and methods In all, 120 patients were enrolled in the study. They were electively planned for laparoscopic cholecystectomy. Their ages were in the range of 21-60 years. Men were 38.3% and women 61.67%. American Society of Anesthesiologists I: 74.17% and II: 25.83%. The patients were randomly allocated into four groups: each of 30 patients. Group M administered magnesium sulfate preoperatively as loading followed by infusion 50 mg/kg/h, group D received dexmedetomidine preoperatively as loading followed by infusion 0.5 µg/kg/h, group L was given lignocaine preoperatively as loading followed by infusion 1 mg/kg/h, and group C received normal saline. Results A significant difference was noticed as regards heart rate changes and mean arterial blood pressure increase between the groups of magnesium sulfate, dexmedetomidine, lignocaine, and the control group at the time of drug administration, after intubation, throughout pneumoperitoneum at 5 min intervals, postpneumoperitoneum, and in the postoperative period after 10 min (P<0.001). Conclusion Magnesium sulfate and dexmedetomidine infusions have comparable effects. Lignocaine was less effective in the attenuation of the hypertensive response of pneumoperitoneum and reducing the dose requirements of opioids during laparoscopic cholecystectomy.